Code-Mixing of Indonesian Language into Geser-Gorom Language in the Comment Section of the Newpilar Seram Bagian Timur Facebook Group - Sidi, Saida; Rumalean, Iwan; Lelapary, Happy (Universitas Pattimura, 2022)
The types, methods, and approaches used in this research are qualitative-descriptive-postpositivism. Aims to describe Indonesian Code Mixing into